Exploration on Curriculum Reform of British and American Literature for English Majors in China’s Provincial Medical University - Li, Zhiqin (Pacific International Journal, 2022)
Abstract: As one of the compulsory courses for English majors, British and American Literature plays an indispensable role in cultivating students’ foreign literature knowledge and literary appreciation competence, as well as improving students’ comprehensive qualities such as humanistic quality and moral sentiment. This paper analyzes the status of British and American Literature Course by demonstrating the existing problems and their causes. Taking the curriculum reform of British and American Literature in a provincial medical university as an example, this paper discusses ways to revise and adjust the Talent Training Program according to the National Standard (for Foreign Language and Literature Majors), puts forwards exploratory strategies on reforming the traditional training mode and creating new mode suitable for the growth needs of students’, aiming to perfect the curriculum system suitable for the university, achieve the goal of talents training and meet the new national requirements of undergraduate education.